Elemental speciation analysis in environmental studies: Latest trends and ecological impact - Llaver, Mauricio (2021)
Speciation analysis is a key aspect of modern analytical chemistry, as the toxicity, environmental mobility, and bioavailability of elemental analytes are known to depend strongly on an element’s chemical species. Henceforth, great efforts have been made in recent years to develop methods that allow not only the determination of elements as a whole, but also each of its separate species. Environmental analytical chemistry has not ignored this trend, and this review aims to summarize the latest methods and techniques developed with this purpose. From the perspective of each relevant element and highlighting the importance of their speciation analysis, different sample treatment methods are introduced and described, with the spotlight on the use of modern nanomaterials and novel solvents in solid phase and liquid-liquid microextractions. In addition, an in-depth discussion of instrumental techniques aimed both at the separation and quantification of metal and metalloid species is presented, ranging from chromatographic separations to electrochemical speciation analysis. Special emphasis is made throughout this work on the greenness of these developments, considering their alignment with the precepts of the Green Chemistry concept and critically reviewing their environmental impact.